Investigation on grid synchronization for grid-tied DC-AC single phase inverters - Shahid, Zeeshan; Khan, Sheroz; Alam, A. H. M. Zahirul; Musse, Mohamud Ahmed (2014)
This paper presents a single-phase Grid-tied inverter for renewable energy systems, which can be used for obtaining small-voltage AC supply for powering small electronic devices or can be used in a distributed grid system for utility supply. The issue of synchronization of these DC-AC inverters with the grid/utility systems is explained and investigated thoroughly in this research. The waveforms generated by each stage of inverter is shown and the issue of power loss caused by variation in phase and frequency due to in-accurate zero crossings is also shown and discussed.